PENGARUH TINGKAT NAUNGAN DAN CEKAMAN AIR TERHADAP PERTUMBUHAN DAN HASIL TEMULAWAK (CURCUMA XANTHORRHIZA) - Ahmad Yunus; Muji Rahayu; Samanhudi Samanhudi; Bambang Pujiasmanto; Iwan Dewangga (Caraka Tani: Journal of Sustainable Agriculture, 2015)
Temulawak (Curcuma xanthorrhiza) is one of superior kind of plant which has many benefits as medicinal plants. Cultivation of temulawak not yet intensively and grown on the land under the trees. Therefore, this research was important to get shade and water stress levels appropriate for cultivation of temulawak and higher producing secondary metabolities. This research used a nested design with two treatment, that is shade (without shade, 25%, 50%, 75%) and water stress (without water stress, 75%, 50%, 25% field capacity) with five replicants. Result were analyzed using analysis of variance and if there significant diference followed by DMRT 5% level. The result showed without shade treatment increase growth of temulawak include number of leaves, fresh weight of plant and dry weight of plants, and shade 50% increase plants height. The treatment of without water stress increase growth and yield of temulawak include number of tillers, number of leaves, fresh weight and dry weight of plants, fresh weight and dry weight of rhizomes. The levels of curcumin increase on shade 25% and water stress 25%.